Comparison of estimates of the nutrient density of the diet of women and children in Uganda by Household Consumption and Expenditures Surveys (HCES) and 24-hour recall - Jariseta, Zo Rambeloson; Dary, Omar; Fiedler, John L.; Franklin, Nadra (SAGE Publications, 2012)
Individual dietary intake data are important for informing national nutrition policy but are rarely available. National Household Consumption and Expenditures Surveys (HCES) may be an alternative method, but there is no evidence to assess their relative performance.To compare HCES-based estimates of the nutrient density of foods consumed by Ugandan women (15 to 49 years of age) and children (24 to 59 months of age) with estimates based on 24-hour recall.The 52 food items of the Uganda 2006 HCES were matched with nutrient content of foods in a 2008 24-hour recall survey, which were used to refine the HCES-based estimates of nutrient intakes. Two methods were used to match the surveys' food items. Model 1 identified the four or five most commonly consumed foods from the 24-hour recall survey and calculated their unweighted average nutrient contents. Model 2 used the nutrient contents of the single most consumed food from the 24-hour recall. For each model, 14 estimates of nutrient densities of the diet were made and 84 differences were compared.Models 1 and 2 were not significantly different. Of the model 2 HCES-24-hour recall comparisons, 67 (80%) did not find a significant difference. No significant differences were found for protein, fat, fiber, iron, thiamin, riboflavin, and vitamin B6 intakes. HCES overestimated intakes of vitamins C and B12 and underestimated intakes of vitamin A, folate, niacin, calcium, and zinc in at least one of the groups.The HCES-based estimates are a relatively good proxy for 24-hour recall measures of nutrient density of the diet. Further work is needed to ascertain nutrient adequacy using this method in several countries.